Diagnóstico del riesgo de precios de transferencia en el sector turístico ecuatoriano de cruceros en las Islas Galápagos durante el periodo 2011. Caso práctico de ajuste - Ruiz Vélez, Luis Javier (2016)
The current global trend toward tax revenue for the countries, especially the emerging and developing countries, aimed at greater collection of direct and progressive taxes, such as income tax from Ecuador. In addition to this, the service of tourism worldwide and in particular in our country has been showing a significant increase in their numbers; and the case of tourism in the Galapagos does not escape this trend. Among the different types of services provided in the Galapagos Islands, the service luxury cruise becomes relevant given the characteristics peculiar to this sector, as in most cases, the Ecuadorian companies providing the same, have their homes matrices in foreign countries, and in some cases, in countries or jurisdictions with lower or low taxation. The fact that the benefits or profits from these activities luxury cruise where the profit margin is higher compared to other tourism services so concerned, they are being sent precisely these countries or jurisdictions with the usual loss of revenue for our country. For these reasons, this research aims to existence of tax risk in financial transactions undertaken by companies that provide the service of cruise tourism in the Galapagos Islands with its related companies domiciled abroad.